ASHRM Board and ERM, 𠄌Walking the Walk𠄍. Issue 4 (April 2015) - Venditti, Ellen Grady
<x xml:space="preserve">Abstract</x> The ASHRM 2015 Board of Directors applied ERM to our Strategic Plan to identify any internal or external threats to the plan by asking a simple question: What could go wrong?